KAJIAN AKTIVITAS OVARIUM BABI LANDRACE DAN BABI BALI HASIL PEMOTONGAN DI RUMAH POTONG HEWAN TRADISIONAL - N. L. G., SUMARDANI; SUBERATA, I W.; ARTININGSIH, N. M.; BUDAARSA, K. (Majalah Ilmiah Peternakan; Vol 21 No 2 (2018): Vol 21, No 2 (2018), 2018)
The reproductive status of sows can be analyzed based on its level of ovarian activities characterized by the presence of a number of follicles and corpus luteum in the ovary. The study of level of ovarium activity of sows observed the level of other reproductive performance. In this study, 100 ovaries in each 50 Landrace and bali sows were divided into three groups of sows weighs slaughtering as of 60-70 kg (A); 71-80 kg (B); and 80-90 kg (C). The variables observed were dimensions of ovary, the number of follicles and corpus luteum in the right and left ovaries. Quantitative data with quantitative t-test determines the comparison on right and left ovary activities. It showed that the average weight of right and left ovaries in landrace sows were 5.70 ± 1.22 g; 6.77 ± 0.96 g, and 4.89 ± 1.47 g; 6.13 ± 1.46 g in bali sows. The average number of dominant follicles on the right and left ovaries of landrace sows were 6.54 ± 1.81 f follicles; 9.78 ± 1.58 follicles, and on bali sows is 5.82 ± 1.90 follicles; 8.91 ± 1.50 follicles. The number of corpus luteum on the right and left ovaries of the Landrace were 5.49 ± 2.22 CL; 8.16 ± 1.86 CL, and on bali sows is 5.27 ± 2.23 CL; 7.69 ± 2.22 CL. The t-test results showed that average number of dominant follicles and corpus luteum in left ovary were significantly greater (P <0.05) compared to the right ovary. The highest percentage of dominant follicles and corpus found in sows of slaughter grouping 80-90 kg (C). It can be concluded that left ovary activity was more active than right ovary, and ovarian activity positively correlated with ovarian weight which indicating ovarian activity in egg cell production and reproductive hormone.